Relação do comportamento de vacas leiteiras no período de transição através de monitoramento remoto com indicadores de saúde, produção e reprodução - Schneider, Vanessa Oliveira de Freitas (2022)
The behavior of dairy cows is the result of their interaction with the physical characteristics of the environment in which they are managed. The ability of vacationers to exhibit natural behaviors is dictated e by farm routines, with the expression of natural behavior being most important to animal health and productivity. Health disorders in the early postpartum period had a substantial proportion of dairy cows in lactation, and directly implicate in comfort, well-being, productivity and reproductive performance. There are several alternatives to be used in monitoring vacations in the transition period however, the ease of implementation and the benefits brought must be analyzed in each technology available for applicability in the properties. Parameters such as rumination and activity were altered and well marked in the second, vacation days before parturition. The work was monitored from July 2018 to August 2019, on a property in the municipality of Boa Vista do Cadeado, northwest of RS. 114 spaces were evaluated, and in 89 animals, the collar data were used. The part is another event in which a behavioral change could be observed and which generated alerts by the system. Remote monitoring of animals generated 65% of warnings. The response variables were subjected to analysis of variance using the Mixed procedure of the SAS® statistical program, considering the fixed effect, evaluation periods, number of deliveries and their interactions, and animals as a random effect. Therefore, the use of a technology that assists in the monitoring of animal health and welfare, allows the intervention to be as early as possible, reducing losses and increasing the profitability of activity, making it an excellent alternative in precision dairy farming.